The Relationship between the Meal Frequency and Functional Dyspepsia in Iranian Adults - Shakiba Hassanzadeh; Parvane Saneei; Ammar Hassanzadeh-Keshteli; Hamed Daghaghzadeh; Ahmad Esmaillzadeh; Peyman Adibi (مجله دانشکده پزشکی اصفهان, 2016)
Background: Limited data are available linking diet-related practices to functional dyspepsia (FD). We aimed to investigate the Relationship between the meal frequency and prevalence of functional dyspepsia among a large sample of Iranian adults.